Information Technology and Systems ICITS 2024, Volume 2 - Rocha, Álvaro; Ferrás, Carlos; Hochstetter Diez, Jorge; Diéguez Rebolledo, Mauricio (Lecture Notes in Networks and Systems, 2024)
XII, 481 p. 146 illus., 116 illus. in color.